Pemanfaatan Teknologi Informasi, Kualitas Informasi dan Penerapan Sistem Informasi Akuntansi pada Kinerja Manajerial BPR Tabanan - Therisyantari, Ni Kadek Rini; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p05, 2022)
Information technology utilization and quality of information in the process of implementing an accounting information system can affect managerial performance. The phenomenon that often occurs is because the system owned by the People's Credit Bank (Bank Perkreditan Rakyat-BPR) in Tabanan has experienced a system failure when sending financial reports to the Financial Services Authority. The purpose of this study is to determine information technology utilization, information quality and application of accounting information systems on the managerial performance of BPR in Tabanan. Population and sample amounted to 23 companies with 46 observations selected using saturated sampling method. The data analysis technique used is multiple linear regression test. This study shows that information technology utilization, information quality and the application of accounting information systems have a positive effect on managerial performance. Keywords: Information Technology Utilization; Information Quality; Application of Accounting Information Systems; Managerial Performance.